2015
DOI: 10.1371/journal.pone.0140017
|View full text |Cite
|
Sign up to set email alerts
|

Job Loss, Unemployment and the Incidence of Hazardous Drinking during the Late 2000s Recession in Europe among Adults Aged 50–64 Years

Abstract: BackgroundTo estimate the incidence of hazardous drinking in middle-aged people during an economic recession and ascertain whether individual job loss and contextual changes in unemployment influence the incidence rate in that period.MethodsLongitudinal study based on two waves of the SHARE project (Survey of Health, Ageing and Retirement in Europe). Individuals aged 50–64 years from 11 European countries, who were not hazardous drinkers at baseline (n = 7,615), were selected for this study. We estimated the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
1
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 42 publications
5
29
1
4
Order By: Relevance
“…For some of the study population, the unexpected association between unemployment and seeking care for AUD might be attributable to job loss or difficulties finding a job due to alcohol consumption. This contrasts however with previous studies which found a positive association between job loss, unemployment and AUD [49,50], especially among people with a higher education level [51].…”
Section: Discussioncontrasting
confidence: 99%
“…For some of the study population, the unexpected association between unemployment and seeking care for AUD might be attributable to job loss or difficulties finding a job due to alcohol consumption. This contrasts however with previous studies which found a positive association between job loss, unemployment and AUD [49,50], especially among people with a higher education level [51].…”
Section: Discussioncontrasting
confidence: 99%
“…Adverse life events, such as divorce and job loss, may increase alcohol consumption 2, 3. Retirement is a further significant life transition when substantial changes in daily life are experienced as retirees adapt to life without work.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, regarding Europe, a longitudinal study was carried out in 11 countries on persons aged 50 to 64 comparing their alcohol consumption habits in 2006 and 2012. The study concluded that loss of employment during the recession was an important risk factor for increased abusive alcohol consumption 22 .…”
Section: Impacts On Risk Factorsmentioning
confidence: 97%